Global Geopolitical Tensions' Impact On The Indonesian Financial Market's Volatility: An Empirical Investigation Of The Ihsg And Rupieh Exchange Rate. - Nurul Susianti Susianti; Tutik Sukmalasari Putri Putri (IQTISHADUNA: Jurnal Ekonomi dan Keuangan Islam, 2025)
This study aims to analyze geopolitical tensions on financial market volatility using empirical studies on JCI and Rupiah exchange rates. The research method used is quantitative with multiple linear regression analysis with VAR model analysis technique. Using the 2nd differencing model, the analysis shows that there is a stable long-run relationship between the three variables, although the short-run relationship is relatively weak. In the long run, JCI and KURS show a significant response to imbalances, while GRI tends to be less responsive. This finding indicates that the effect of the GRI on the CURS only becomes apparent gradually over a longer period of time. One important finding is that the contribution of the GRI to changes in the KURS increases gradually, reaching almost 25% in certain periods, with the effect of KURS on itself (D(KURS,2)) in the range of 70-90%. The results of this study emphasize the importance of global external influences in exchange rate dynamics, as well as the need for economic policies that consider the long-term linkages between these variables.